The Impact of Fishbone Strategy in the Achievement of Chemistry and Visual Thinking Among the Seven Grade Students - DURAID AHMED, Susan (Utopía y Praxis Latinoamericana, 2020)
ABSTRACTThe current research aims to know the effect of fishbone strategy on achievement of chemistry and visual thinking among middle school students, the research sample consisted of 89 students divided into two experimental groups consisting of 44 students who studied fishbone strategy, and a control group that consisted of 45. A student studied in the usual way; the two groups were rewarded in a number of variables, and the researcher built two tools for the research: the first is an achievement test consisting in 30 paragraphs, and the second is a visual thinking test consisting in 18 paragraphs.